Fluorescent organic nanoparticles (FONs) as convenient probes for metal ion detection in aqueous medium. Issue 8 (13th March 2019) - Ahmed, Mukhtiar; Faisal, Muhammad; Ihsan, Ayesha; Naseer, Muhammad Moazzam
Abstract : Fluorescent organic nanoparticle (FON)-based chemosensors are emerging as a valuable tool for the fast and accurate detection of metal ions in aqueous media. In this review, we highlight the recent developments in this field. Abstract : Recently, water contamination caused by metal ions has become one of the most serious problems as it has caused several deaths and socioeconomic problems around the world. Hence, the fast and accurate detection of metal ions in aqueous media has become the most important area of research; from time to time, new probes have been designed for this purpose. Among the previously reported sensors, probes based on fluorescent organic nanoparticles (FONs) have been gaining tremendous attention due to their ease of preparation/fabrication, synthetic diversity according to targeted metal ions, quick response, high selectivity toward different analytes at lower concentrations, tenable optical properties, and less toxicity. This review comprises two main sections, wherein we have tried to summarize the key progresses made in this field. The first section summarizes the literature dealing with FON-based chemosensors, which are used for the detection of transition metal ions of silver, copper, chromium, cadmium, mercury, iron, and zinc. The second section focuses on FON-based chemosensors that have been used for the detection of main group metal ions, namely, cesium, aluminum, strontium, lithium, and tin. Further, this review provides an adequate amount of information about the mechanism of metal ion sensing with FONs. It is expected that this review can provide sufficient information about this area of research and will be useful in fruitful progress in this field in the future.